1965
DOI: 10.1679/aohc1950.25.435
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Electron Microscopic Studies of the Parathyroid Gland

Abstract: Abstract.An electron microscopic observation has been made on the normal parathyroid glands of the monkey (Macaca mulatta fascicularis) and dog.The parathyroid glands of each animal were exstirpated under anesthesia with chloroform (by monkey) or thiopental sodium (by dog). Small pieces of the gland were fixed for one hour in 2.5% osmium tetroxide solution, which was adjusted to PH 7.4 with phosphate buffer. After dehydration in increasing concentration of alcohols, specimens were embedded in epoxy resin by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In the parathyroid cells, abundant free or membrane-attached ribosomes, well-developed Golgi complex, many amorphous, electron-dense vesicles, and widespread interdigitation of the plasma membranes were noted. Such fine structural characteristics are consistent with those of enhanced synthesizing and secretory activity of the parathyroid cells (Nakagami, 1965;Roth and Raisz, 1966;Zawistowski, 1966;Altenaehr et al, 1969). Therefore, it seems reasonable to assume that these cells produce large amounts of secretory material which accumulates in the intercellular spaces.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the parathyroid cells, abundant free or membrane-attached ribosomes, well-developed Golgi complex, many amorphous, electron-dense vesicles, and widespread interdigitation of the plasma membranes were noted. Such fine structural characteristics are consistent with those of enhanced synthesizing and secretory activity of the parathyroid cells (Nakagami, 1965;Roth and Raisz, 1966;Zawistowski, 1966;Altenaehr et al, 1969). Therefore, it seems reasonable to assume that these cells produce large amounts of secretory material which accumulates in the intercellular spaces.…”
Section: Discussionsupporting
confidence: 69%
“…A number of electron-microscopic studies of the parathyroid glands indicate that a high level of plasma calcium is associated with diminished, and a low level with increased, activity of the parathyroid cells (Lever, 1957 and1958 ;Roth and Munger, 1962;Munger and Roth, 1963;Roth and Raisz, 1966;Nakagami, 1967;Roth et al, 1968). It has also been demonstrated that high doses of vitamin-D (Capen et al, 1965 and or a combination of excessive amounts of vitamin-D and calcium (Roth et al, 1968) suppress parathyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…The parathyroid gland of the rat is composed of a single type of cells (1)(2)(3)(4)(5) . These are similar to the chief cells of man (6)(7)(8) and other species (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and are presumed to elaborate the hormone of the gland . This hormone has been identified as a protein (23) ; and active protein synthesis in the cells has been suggested by radioautographs showing uptake of label from bicarbonate-11C ( Fig .…”
mentioning
confidence: 74%
“…The cells of a given parathyroid gland have been assumed to be in different functional states, with some of them active and others not (4,8,9,14,22) . However, silver grains appeared uniformly distributed in light microscope radioautographs following tyrosine-3H or galactose-3H injection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation